Model Sistem Informasi Manajemen Sekolah Berbasiskan Notasi Unified Modeling Language - Kurniawan, Yohannes (Bina Nusantara University, 2013)
Basically the use of integrated information systems can be applied not only for the company, but also education industry, particularly schools. To support business processes at the school, this research would like to describe a conceptual model of information systems using the Unified Modeling Language (UML) notationwith